中国加入WTO后辽源工业面临的影响及对策分析 = Strategical analysis for industries in Liaoyuan city after China's accession to WTO - 赵阳 Zhao, Yang (2008)
It is necessary for China to join the World Trade Organization (WTO) as to be in line with world way of operation and integrated with world economy. The purposes of this thesis are to 1) study the development of industries in Liaoyuan city and 2) propose possible strategies for their sound development in the future.